KNOWLEDGE, ATTITUDE, AND PRACTICE (KAP) SURVEY ON ONLINE LEARNING AMONG UNIVERSITY STUDENTS IN MALANG - Rosi, Rois Imron (Proceeding of International Conference on Islamic Education (ICIED), 2021)
This study is a Knowledge, Attitude, and Practice (KAP) survey on online learning among university students in Malang. This study is an advanced study conducted in the beginning of the implementation of online learning during covid-19 pandemic era. In the end of its implementation and after the official letter from ministry of education and culture number 4, 2021 regarding the allowance of limited face-to-face learning in university, this study might be useful in the development of Indonesian education in the future of digitalization era. This study is tried to examine student’s understanding, their assessment, and their practice of online learning during its implementation. The respondent of this study are 395 students from five universities in Malang. The result of this study stated that all students have understood the meaning of online learning that in line with scholars’ definitions. There are also many platforms that have known by students such as Google meet, Zoom, University’s e-learning, Schoology, Jitsi, Webex, Spada Dikti, Big Blue Button, Discord, and so forth. Regarding student’s assessment, Students have identified the advantages and disadvantages of online learning. The advantages are; flexibility, increasing student’s technological ability, safety from covid-19, and ease of access while the disadvantages are; lack of material understanding, internet network problem, physical Fatigue, psychological problem, and internet quota. In the practical area, google meet, zoom, and whatsapp are the most often used by lecturer. Those platforms are also identified by students as the most effective media for online teaching and learning process.